Study the Effect of using RAP in Warm Mix Asphalt Pavement. (Journal of Engineering, 2023)
Sustainability is providing the needs without compromising the ability of the strategical forming to meet their requirements. The production of warm asphalt mixtures using recycled pavements produces economic and environmentally friendly mixtures, which is the most important advantage of this work. This research aims to determine the effect of recycled asphalt concrete (RAP) on the indirect tensile strength of warm asphalt mixtures and Marshall Properties. Models of warm asphalt mixtures using Aggregate from the Al-Nibaay quarry, Asphalt with a degree of penetration (40-50) from the refinery of the cycle, and obtained Recycled asphalt concrete from Salah Al-Din Road, Al-Ameriya area in Baghdad are prepared. Use five ratios of (0, 10, 20, 30, and 40%) of recycled asphalt concrete. Marshall Design method is adopted to estimate the perfect existence of the asphalt cement for sample preparation.  The mixtures properties, volumetric properties, and indirect tensile strength test are evaluated to assess bonding strength. Results show that the increase in the replacement percentage of RAP causes an increase in flow and air void and decreases the bulk density, voids in mineral aggregate (VMA), and voids filled with Asphalt (VFA).  Stability increases with increased RAP content until it reaches its peak and falls. The highest stability value is at 30% RAP by 58%, about the indirect tensile strength test. The increase in the RAP ratio increases the tensile strength and the bonding between the components. So including RAP material in warm asphalt mixtures improves properties and meets performance requirements.